Developing a self‐assessment instrument to evaluate practice‐readiness among student pharmacists. (6th December 2021) - Ford, Channing R.; Astle, Kevin N.; Kleppinger, Erika L.; Sewell, Jeanna; Hutchison, Amber; Garza, Kimberly B.
Abstract: This chapter explores the role of self‐assessment in the development of professional identity formation within student pharmacists.